Comparative analysis of optic disc and macular microvasculature in children with anisometropic amblyopia before and after treatment - Jia-Hao Li; Chen-Yu Yang; Jia-Yu Ma; Jing Wang; Ying-Jun Li (Photodiagnosis and Photodynamic Therapy)
Purpose: To evaluate optic disc and macular microvasculature changes in children with anisometropic amblyopia before and after treatment. Methods: In all, 60 children with unilateral anisometropic amblyopia between the ages of 6 and 12 were randomly selected from the ophthalmology clinic of Fuyang People's Hospital, while 60 children with non-amblyopia in the same age range were randomly selected as a normal control group. The right eye was uniformly taken in the control group with at least 6 months of follow-up. Optical coherence tomography angiography (OCTA) was used to evaluate the macular vessel density of superficial capillary plexus (SCP) and deep capillary plexus (DCP), optic disc vascular density (VD), foveal avascular zone (FAZ) area, macular thickness, and retinal nerve fiber layer thickness (RNFLT). Results: Before treatment, the vessel density of the optic disc, macular SCP and DCP in the amblyopic group was significantly lower than those in the fellow eyes and the control group (P < 0.05), while there were no statistically significant differences in the vessel densities of the optic disc, macular SCP and DCP between the amblyopic eyes, the fellow eyes, and the control group after treatment (P > 0.05). Statistically significant negative correlations were found between the alterations of BCVA in amblyopic eyes and the alterations of the vessel densities of the optic disc, macular SCP and DCP in amblyopia eyes (P < 0.05) except for superior nasal (SN) and inferior nasal (IN) regions of the optic disc radial peripapillary capillary, temporal and nasal regions of macular parafoveal SCP, nasal regions of macular parafoveal DCP and inferior regions of macular perifoveal DCP (P > 0.05). Conclusion: Macular and optic disc vessel density in OCTA are lower in children with anisometropic amblyopia and tend to return to normal levels to a certain extent following treatment for amblyopia.